2012
DOI: 10.1007/s10327-012-0371-0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Ralstonia solanacearum bacterial wilt disease by an organic hydroponic system

Abstract: An organic hydroponic system that we developed has potential to control root diseases including bacterial wilt of hydroponically grown tomato. In inoculation tests with Ralstonia solanacearum during tomato plant cultivation in conventional inorganic hydroponics and in our organic system, many of the tomato seedlings in the conventional system wilted and died, but none of the seedlings in the organic hydroponics wilted or developed any symptoms, suggesting that the organic system can suppress this bacterial wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 9 publications
1
43
0
Order By: Relevance
“…Furthermore, microbial diversity can be beneficial for plants. The presence of some mutualistic microorganisms in the plant biosphere can retard the development of pathogens [34,89,90] while promoting growth (e.g., plant growth-promoting rhizobacteria and plant growth-promoting fungi).…”
Section: Pest and Disease Managementmentioning
confidence: 99%
“…Furthermore, microbial diversity can be beneficial for plants. The presence of some mutualistic microorganisms in the plant biosphere can retard the development of pathogens [34,89,90] while promoting growth (e.g., plant growth-promoting rhizobacteria and plant growth-promoting fungi).…”
Section: Pest and Disease Managementmentioning
confidence: 99%
“…Furthermore, microbial diversity can be beneficial for plants. The presence of some mutualistic microorganisms in the plant biosphere can retard the development of pathogens (Bulgarelli et al, 2013;Fujiwara et al, 2013Fujiwara et al, , 2012 while promoting growth (e.g. plant growth-promoting rhizobacteria and plant growth-promoting fungi).…”
Section: Pest and Disease Managementmentioning
confidence: 99%
“…The pathogen favors cool and moist conditions, and is extremely difficult to control (van Kan 2005;Williamson et al 2007;Shishido 2011;Shim et al 2014). Organic hydroponics, which use corn steep liquor (CSL) as a nutrient source (Shinohara 2006;Shinohara et al 2011), were developed to control bacterial (Fujiwara et al 2012) and fungal soil-borne (Chinta et al 2014) diseases. Thus, this specific type of hydroponic cultivation may become a potential disease management method for B. cinerea infection.…”
Section: Research Articlementioning
confidence: 99%
“…Thus, this specific type of hydroponic cultivation may become a potential disease management method for B. cinerea infection. Previous research has shown that CSL promotes the growth of a beneficial microbial community (Shinohara 2006;Shinohara et al 2011;Fujiwara et al 2012;Chinta et al 2014). These microbes rapidly colonize the nutrient solution and rhizosphere of the cultivated plants (Valance et al 2010).…”
Section: Research Articlementioning
confidence: 99%